Tantangan Implementasi Rekam Medis Elektronik di Puskesmas - Hammam Abror Asminoto; Achmad Jaelani Rusdi; Anis Ansyori (Jurnal Kesehatan Amanah, 2024)
This study aims to identify the extent to which the Health Center is ready for the implementation of Electronic Medical Records. The methodology applied in this study is Literature Review. The data sources used are secondary data collected from various literature sources available on the internet. The journal used is a reputable publication and focuses on the theme of readiness to implement electronic medical records at the Health Center. The collection of journals was carried out with inclusion criteria that included Population, Intervention, Comparator, Results, Time, Study Design, and Language, so that the total journals analyzed in this study reached 10 Journals. The readiness in the implementation of electronic medical records seen from the aspect of human resources in the Puskesmas shows that they are not fully prepared, because there are still several challenges such as the shortage of medical personnel responsible for medical records and the mismatch between the educational background of employees and the tasks carried out. In terms of cost, the Puskesmas is quite ready for the implementation of electronic medical records and no obstacles were found in terms of funding. In terms of materials, the Puskesmas is not fully prepared, because there are still several problems faced, such as the lack of computers, network problems that are often unstable, and system disruptions that cause errors. In the mechanical aspect, the health center showed quite good readiness, with the results of the study showing that the health center developed more electronic medical record systems using the waterfall approach. However, there are no health centers that implement an electronic system for RME developed by the Ministry of Health in this study. In terms of methodology, the Puskesmas is quite ready, which can be evidenced by the existence of Standard Operating Procedures (SOP) for the implementation of Electronic Medical Records in several Puskesmas.